2011
DOI: 10.1073/pnas.0906930108
|View full text |Cite
|
Sign up to set email alerts
|

Homozygously deleted gene DACH1 regulates tumor-initiating activity of glioma cells

Abstract: Loss or reduction in function of tumor suppressor genes contributes to tumorigenesis. Here, by allelic DNA copy number analysis using single-nucleotide polymorphism genotyping array and mass spectrometry, we report homozygous deletion in glioblastoma multiformes at chromosome 13q21, where DACH1 gene is located. We found decreased cell proliferation of a series of glioma cell lines by forced expression of DACH1. We then generated U87TR-Da glioma cells, where DACH1 expression could be activated by exposure of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
47
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 48 publications
5
47
1
Order By: Relevance
“…Clinical studies have also demonstrated a correlation between poor prognosis in breast cancer patients and reduced DACH1 expression (42). Similar to what we observed for ZNF326 in TNBC cells, forced expression of DACH1 in glioma cell lines also resulted in decreased proliferation in vitro and tumor growth in vivo (39). Likewise, glioma-DACH1-low cells form spheroids in serum-free medium whereas parental glioma cells do not.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Clinical studies have also demonstrated a correlation between poor prognosis in breast cancer patients and reduced DACH1 expression (42). Similar to what we observed for ZNF326 in TNBC cells, forced expression of DACH1 in glioma cell lines also resulted in decreased proliferation in vitro and tumor growth in vivo (39). Likewise, glioma-DACH1-low cells form spheroids in serum-free medium whereas parental glioma cells do not.…”
Section: Discussionsupporting
confidence: 70%
“…These results strongly support the hypothesis that ZNF326 is a TS gene that regulates CSC self-renewal by directly controlling the expression of genes important for CSC self-renewal. Additional support for this hypothesis has been provided by other laboratories who have shown that DACH1 inactivation increases the number of CSCs in glioma and breast cancer, whereas Gata3 negatively regulates CSCs from luminal progenitors (39)(40)(41). Clinical studies have also demonstrated a correlation between poor prognosis in breast cancer patients and reduced DACH1 expression (42).…”
Section: Discussionmentioning
confidence: 53%
“…In addition, DACH1 associates with the estrogen and androgen receptors (ER and AR) to regulate signal transduction and proliferation of breast and prostate cancer cells [17,18]. DACH1 inhibits EMT and tumor initiated cells in breast cancer and glioma [19-21]. DACH1 can directly associate with p53 and enhance its function in breast and lung cancer [10,22].…”
Section: Introductionmentioning
confidence: 99%
“…DACH1 can directly associate with p53 and enhance its function in breast and lung cancer [10,22]. Inactivation of DACH1 in human cancer tissues was observed by mechanisms of gene deletion, mutation, or promoter hypermethylation [21,23]. Clinically, a decreased expression of DACH1 in breast and endometrial cancer correlates with tumor progression, poor differentiation [23] and predicts a short survival [13,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…DACH1 is also frequently methylated in human colorectal cancer and methylation of DACH1 may serve as detective and prognostic marker in colorectal cancer . DACH1 regulates FGF2 (4q27)-mediated tumor-initiating activity of glioma cells and inhibits formation of tumor-initiating spheroids of glioma cells (Watanabe et al, 2011).…”
Section: Dach1mentioning
confidence: 99%